Nonlinear dynamic analysis of concrete gravity dam - Stevcho Mitovski, Ljupcho Petkovski, Frosina Panovska (Macedonian Committee on Large Dams, 2021)
Pine Flat Dam, located on King’s River, California, was constructed by the US Army Corps of Engineers in 1954 with height of 122 m. In the paper is carried out nonlinear dynamic analysis of the dam under action of ETAF (Endurance Time Acceleration Function) excitation record. The numerical analysis was carried out by plane (2D) model, that actually is spatial model at 1m’, by application of code SOFiSTiK.
Keywords: Pine Flat Dam, numerical analysis, nonlinear dynamic analysis.